2021
DOI: 10.1177/10598405211069601
|View full text |Cite
|
Sign up to set email alerts
|

Period Product Insecurity, School Absenteeism, and use of School Resources to Obtain Period Products among High School Students in St. Louis, Missouri

Abstract: Menstrual hygiene management (MHM) among female students is a neglected public health issue in the U.S. This study documented period product insecurity, school absenteeism, and use of school resources to obtain period products among high-school students in St. Louis, MO. Female students completed an anonymous, self-administered survey in English (n = 119). Descriptive statistics were used to determine the prevalence of period product need, resources used to obtain period products, and period-related absenteeis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…School nurses also know students who miss school because of their period. This finding corresponds with studies of students' self‐reported attendance at a high school in St. Louis, which found that over 70% of students missed school for any reason related to their period in the previous school year, and nearly 70% missed at least 1 day per month as a result of their periods in the current school year 4,5 . They are also consistent with findings by Cotropia 6 that showed a lack of access to period products at school resulted in students missing school, coming late, leaving early, and negatively affecting their ability to learn.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…School nurses also know students who miss school because of their period. This finding corresponds with studies of students' self‐reported attendance at a high school in St. Louis, which found that over 70% of students missed school for any reason related to their period in the previous school year, and nearly 70% missed at least 1 day per month as a result of their periods in the current school year 4,5 . They are also consistent with findings by Cotropia 6 that showed a lack of access to period products at school resulted in students missing school, coming late, leaving early, and negatively affecting their ability to learn.…”
Section: Discussionsupporting
confidence: 89%
“…Again, these results from school nurses align with self-reported data from students, where nearly 60% in 1 study said they wanted more information and education around managing their periods and about half in a follow-up study reported the same. 4,5 Our findings also align with focus group themes identified by Secor-Turner and colleagues, 11 who found that while students learned about anatomy and physiology in school, they learned little about menstruation management and how to use period products.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Disparities in access to menstrual products are heightened for students from low-income households or students experiencing homelessness (Michel et al, 2022). Consequently, at-risk menstruating students have the added burden of missing school days or leaving school early and can potentially suffer from mental health issues due to a lack of menstrual support and equipment in schools (Cardoso et al, 2021; Cotropia, 2019; Gouvernet et al, 2023; Kuhlmann et al, 2021; Oster & Thornton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In addition to health concerns, heavy menstrual bleeding can be associated with negative social, economic, and environmental consequences. 10,11 A menstruating individual without heavy menstrual bleeding is estimated to use up to 10,000 pads in their lifetime. 12 Many of the new, reusable menstrual products offer alternatives for menstrual containment that reduce environmental waste, but little is known about how well they function for individuals with heavy menstrual bleeding.…”
mentioning
confidence: 99%